THE IDEOLOGY OF DONALD TRUMP ON HIS SPEECH AT THE ISRAEL MUSEUM: FAIRCLOUGH’S THREE MODELS OF CDA - Faiz, Ahmad; Chojimah, Nurul; Khasanah, Ismatul (Jurnal Penelitian Humaniora, 2020)
This research investigated the ideology of Donald Trump on his speech at the Israel museum. This research focused on analysing illocutionary acts to discover the ideology of Trump on his speech. This research used qualitative approach. The design of this research is Critical Discourse Analysis (CDA). This research used Fairclough’s three models of CDA, namely: textual analysis, discursive practice and social practice The result that showed there were five types of illocutionary acts expressed, those are representatives, directives, commissives, expressives and declaratives. Representatives was mostly expressed by Trump. Therefore, the result showed that Trump expressed all types of illocutionary act. The ideology on the speech at the Israel museum showed that Trump intended to use his power to create peace in Jerusalem.